A 5-year comparison of marginal bone level following immediate loading of single-tooth implants placed in healed alveolar ridges and extraction sockets in the maxilla - Berberi, Antoine N.; Sabbagh, Joseph (Frontiers in Physiology, 2014)
Abstract Purpose: The aim of present investigation was to evaluate marginal bone level after 5-year follow-up of implants placed in healed ridges and fresh extraction sockets in maxilla with immediate loading protocol. Materials and Methods: Thirty-six patients in need of a single tooth replacement in the anterior maxilla received 42 Astra Tech implants (Astra Tech Implant system™, Dentsply Implants, Mölndal, Sweden). Implants were placed in healed ridges (group I) or immediately into extraction sockets (group II). Implants were restored and placed into functional loading immediately by using a prefabricated abutment. Marginal bone level relative to the implant reference point was recorded at implant placement, crown cementation, 12, 36 and 60 months following loading using intra-oral radiographs. Measurements were made on the mesial and distal sides of each implant Results: Overall, two implants were lost from the group II, before final crown cementation: they were excluded from the study and all remaining implants osseointegrated successfully after 5 years of functional loading. The mean change in marginal bone loss after implant placement was 0.267±0.161 for one year, and 0.265±0.171 for three years and 0.213±0.185 for five years in extraction sockets and was 0.266±0.176 for one year and 0.219±0.175 for three years and 0.194±0.172 for five years in healed ridges group. Significant reduction of marginal bone loss was more pronounced in implants inserted in healed ridges (P